Analysis Of Foreign Citizens In The Analysis Of Visit Visa-Free Policy On The Tourism Sector In Bali (Intelligence Study Perspective) - Khotimah, Husnul; Hanita, Margaretha; Yoesgiantoro, Donny (GEMA EKONOMI, 2022)
Tourism is the temporary movement of groups or individuals between locations for the purpose of pleasure and personal interest. In the development of tourism between countries, there are rules that apply to government permits in maintaining security against foreign visits to the country. This research uses intelligence theory and surveillance theory. The methodology used is a qualitative approach. This research is the result of observation and research, it is found that there are significant benefits to the economy and avoid the adverse effects of law violations through cases of illegal labor committed by tourists to human trafficking and narcotics which are bad impacts to social issues related to local people's own concerns over the emergence of illegal or legal foreign tour guides that can damage the local wisdom of the local community if the tour guide does not understand the values ​​of local wisdom that exist in each tourist destination